Association of Down syndrome with major congenital anomalies in the North Indian population - Kanchan Bisht; Rakesh Kumar Verma; Navneet Kumar; Shakal Narayan Singh; Baibhav Bhandari (Wolters Kluwer Medknow Publications, 2021)
Context: Down syndrome (DS), which usually occurs due to an extra chromosome 21 or a partial trisomy, is the most common genetic cause of intellectual disability. The affected individuals usually present with characteristic clinical manifestations and are seen to be associated with various systemic defects. Aim: The aim of our study was to determine the major congenital anomalies associated with DS in the North Indian population. Methods: Blood samples of 51 children (0-10 years) who were screened for the suspicion of DS were collected. Karyotyping was conducted. Data were analyzed using the Statistical Package for the Social Sciences (SPSS) software version 21.0. Results: Out of the 51 suspected participants, karyotypes could be successfully obtained only for 40. Among these 40 participants, karyotypes of 35 were confirmed to be DS. Of these 35 confirmed cases, 21 (60%) were found to be associated with at least one major congenital anomaly, of which cardiac anomalies (34.2%) were most common, followed by gastrointestinal tract and genitourinary anomalies (11.4% each). Central nervous system and musculoskeletal anomalies constituted 5.7% each. Mosaic variant of DS was found to be least associated with congenital anomalies. Conclusion: The patients with DS should be carefully examined for systemic anomalies. Most cases are usually associated with at least one congenital anomaly.